Investor and Assuror perspectives on materiality for sustainability reporting: An exploratory case study of Nigeria's oil and gas industry - Nnodim, Osai Simeon (University of Dundee, 2022)
This thesis utilises the materiality concept of accounting to investigate institutional investor and assuror practitioner perspectives on sustainability reporting in the Nigerian oil and gas sector. The outcome of this investigation is expected to provide some insight into the prospects of success for the Nigerian financial sector’s drive to normalise sustainability reporting. For this purpose, a qualitative case study research was undertaken, which involved interviews of investors in decision making roles and auditors with social and/or environmental audit experience, and the content and narrative analyses of oil company sustainability disclosures.

The main findings of this thesis indicate that the materiality decision for social and environmental issues is arrived at by considering the impacts on and of the company, the interests of influential stakeholder groups, and the unique socio-cultural attitudes of the region. The perspectives of both investor and assuror stakeholder groups are positively associated, implying that this decision model is likely to hold for both groups. Evidence was found suggesting that institutional forces are driving investor and assuror understandings of corporate sustainability, and that investors are unaware of their power to influence sustainability reporting adoption. Evidence was also found that investors have a culture of secrecy. It was also found that oil company narratives are structured in a manner that manages impressions and reduces reputation risk.

Additionally, there are suggestions from the data that an information needs gap exists between the oil companies that prepare sustainability reports and the investors and assurors that use them. This disconnect implies that the normalisation of sustainability reporting in Nigeria is a work in progress that is untenable in the short term.